MULTICULTURAL COMPETENCE AND PERFORMANCE OF GOVERNMENT APPARATUS: THE EMPIRICAL STUDY IN LAMPUNG PROVINCE - Suyanto, Suyanto; Hendri, Nedi (Journal of Community Research and Service, 2018)
AbstractThis study was Carried out to analyze the effects of multicultural competence models consisting of understanding, attitude and individual skill on the performance of government apparatus. The study applied a survey method with the survey subject of regent and municipal Civil Servants of Lampung Province. Samples determination was based on a purposive sampling technique. The study collected 127 respondents. Analysis on the Data used a Structural Equation Model (SEM) operated under AMOS application program. This empirical result proved a direct effect on understanding between attitude; attitude on skills; and skills on the performance of the government apparatus. The Study Also Showed an attitude and skills as mediation between understanding the indirect effect on the performance of the government apparatus. However, the direct effect on understanding between skills and attitudes on performance was insignificant. Finally, this result implies that multicultural understanding alone is not sufficient to Determine the performance of government apparatus, but it takes attitude and skills to respond in different cultural Contexts. Reviews these results might be used to develop a unified theory effects on multicultural competence.Keywords: competence, multicultural, performance.